Methylene Blue for Refractory Shock in Children: A Systematic Review and Survey Practice Analysis. Issue 6 (June 2020) - Otero Luna, Andrea V.; Johnson, Rachel; Funaro, Melissa; Canarie, Michael F.; Pierce, Richard W.
Abstract : Objectives: Shock refractory to fluid and catecholamine therapy has significant morbidity and mortality in children. The use of methylene blue to treat refractory shock in children is not well described. We aim to collect and summarize the literature and define physicians' practice patterns regarding the use of methylene blue to treat shock in children. Design: We conducted a systematic search of MEDLINE, Embase, PubMed, Web of Science, Cochrane for studies involving the use of methylene blue for catecholamine-refractory shock from database inception to 2019. Collected studies were analyzed qualitatively. To describe practice patterns of methylene blue use, we electronically distributed a survey to U.S.-based pediatric critical care physicians. We assessed physician knowledge and experience with methylene blue. Survey responses were quantitatively and qualitatively evaluated. Setting: Pediatric critical and cardiac care units. Patients or Subjects: Patients less than or equal to 25 years old with refractory shock treated with methylene blue. Interventions: None. Measurements and Main Results: One-thousand two-hundred ninety-three abstracts met search criteria, 139 articles underwent full-text review, and 24 studies were included. Studies investigated refractory shock induced by a variety of etiologies and found that methylene blue was generally safe and increased mean arterial blood pressure. There is overall lack of studies, low number of study patients, and low quality of studies identified. Our survey had a 22.5% response rate, representing 125 institutions. Similar proportions of physicians reported using (40%) or never even considering (43%) methylene blue for shock. The most common reasons for not using methylene blue were unfamiliarity with this drug, its proper dosing, and lack of evidentiary support. Conclusions: Methylene blue appears safe and may benefit children with refractory shock. There is a stark divide in familiarity and practice patterns regarding its use among physicians. Studies to formally assess safety and efficacy of methylene blue in treating pediatric shock are warranted. Abstract : Supplemental Digital Content is available in the text.